Does microfinance model determine the effectiveness of microfinance intervention in enhancing microenterprise performance? Evidence from Bank Rakyat Indonesia - Hawariyuni, Weni; Kassim, Salina (Faculty of Islamic Economics and Business, Ar-Raniry State Islamic University, Banda Aceh, Indonesia, 2016)
This study aims to investigate the effectiveness of different microfinance model in enhancing the performance of microenterprises in terms of income, fixed assets, and household expenditures. By focusing on the case of Bank Rakyat Indonesia, one of the most successful commercial microfinance providers in the world, two types of microfinance products, namely KUPEDES and KUR are being compared. The KUPEDES is original product of BRI Unit, while the KUR is a micro-product subsidized by the Indonesian government. Based on the experience of BRI Unit in Medan city, Indonesia, we assess the impact of microfinance intervention on 400 clients. The findings demonstrated that KUPEDES as original microproduct is more successful compared to KUR product in enhancing the performance of microenterprise through income, fixed assets, and household expenditures as successful indicators.